PERAN KEPALA SEKOLAH DALAM PENGEMBANGAN BUDAYA KEAGAMAAN DI SMPN 1 KALIWEDI KABUPATEN CIREBON - Jumrud Khaeriyah (Edulead : Journal of Education Management, 2021)
This reserch aims to: (1) Knowing the contribution of the strategic role of the principal's leadership in developing religious culture at SMPN 1 Kaliwedi, Cirebon Regency, (2) Get a description of the implementation of the principal's leadership competence in developing religious culture at SMPN 1 Kaliwedi, Cirebon Regency, and (3) Revealing objective facts about the principal's efforts in developing religious culture at SMPN 1 Kaliwedi, Cirebon Regency. This research has been applied the study case with the qualitative approch. Data collection has been done through interviews, observations, and documentation. The subjects of this research are the principal. The data analysis technique which used is the Miles and Huberman model which consists of data reduction, data presentation, and conclusion. The results of the research was found that: (1) The strategic role of the principal's leadership in developing a religious culture in schools always provides support and the best role model in carrying out transparent and accountable school management. The main tasks and leadership functions are carried out with full of dedication, (2) Implementation of the principal's leadership competence in developing religious culture at SMPN 1 Kaliwedi, Cirebon Regency through extracurricular activities of Islamic Education, The principal acts as democratic and transparent leaders in encouraging religious activities in schools, and (3) The principal's efforts to develop religious culture at SMPN 1 Kaliwedi, Cirebon Regency are provide the best role model for all school members, school management is formulated together, and school residents are involved in socializing the religious culture development program at SMPN 1 Kaliwedi, Cirebon Regency. Abstrak Penelitian ini bertujuan untuk: (1) Mengetahui kontribusi peran strategis kepemimpinan kepala sekolah dalam mengembangkan budaya keagamaan di SMPN 1 Kaliwedi Kabupaten Cirebon, (2) Mendapatkan deskripsi tentang implementasi kompetensi kepemimpinan kepala sekolah dalam mengembangankan budaya keagamaan di SMPN 1 Kaliwedi Kabupaten Cirebon, dan (3) Mengungkap fakta obyektif tentang upaya kepala sekolah dalam pengembangan budaya keagamaan di SMPN 1 Kaliwedi Kabupaten Cirebon. Penelitian ini menggunakan studi kasus dengan pendekatan kualitatif. Pengumpulan data dilakukan melalui wawancara, observasi, dan dokumentasi. Subjek penelitian ini yaitu kepala sekolah. Teknik analisis data yang digunakan yaitu model Miles dan Huberman yang terdiri atas reduksi data, penyajian data, dan kesimpulan. Hasil penelitian didapatkan bahwa: (1) Peran strategis kepemimpinan kepala sekolah dalam mengembangkan budaya keagamaan di sekolah selalu memberikan dukungan dan peneladanan dalam menjalankan manajemen sekolah yang transparan dan akuntabel. Tugas pokok dan fungsi kepemimpinannya dilaksanakan dengan penuh dedikasi, (2) Implementasi kompetensi kepemimpinan kepala sekolah dalam mengembangankan budaya keagamaan di SMPN 1 Kaliwedi Kabupaten Cirebon melalui kegiatan ekstrakurikuler Pendidikan Agama Islam, kepala sekolah berperan sebagai pimpinan yang demokratis dan transparan dalam mendorong kegiatan keagamaan di sekolah, dan (3) Upaya kepala sekolah terhadap pengembangan budaya keagamaan di SMPN 1 Kaliwedi Kabupaten Cirebon adalah dengan memberikan teladan terbaik kepada seluruh warga sekolah, manajemen sekolah dirumuskan secara bersama-sama, dan warga sekolah dilibatkan dalam sosialisasi program pengembangan budaya keagamaan di SMPN 1 Kaliwedi Kabupaten Cirebon.